Pediatric cardiomyopathies: causes, epidemiology, clinical course, preventive strategies and therapies. (November 2013) - Lipshultz, Steven E; Cochran, Thomas R; Briston, David A; Brown, Stefanie R; Sambatakos, Peter J; Miller, Tracie L; Carrillo, Adriana A; Corcia, Liat; Sanchez, Janine E; Diamond, Melissa B; Freundlich, Michael; Harake, Danielle; et al.
Pediatric cardiomyopathies, which are rare but serious disorders of the muscles of the heart, affect at least one in every 100, 000 children in the USA. Approximately 40% of children with symptomatic cardiomyopathy undergo heart transplantation or die from cardiac complications within 2 years. However, a significant number of children suffering from cardiomyopathy are surviving into adulthood, making it an important chronic illness for both pediatric and adult clinicians to understand. The natural history, risk factors, prevalence and incidence of this pediatric condition were not fully understood before the 1990s. Questions regarding optimal diagnostic, prognostic and treatment methods remain. Children require long-term follow-up into adulthood in order to identify the factors associated with best clinical practice including diagnostic approaches, as well as optimal treatment approaches. In this article, we comprehensively review current research on various presentations of this disease, along with current knowledge about their causes, treatments and clinical outcomes.